Robust Design of Intrusion Detection System in Wireless Mobile Adhoc Network (RDIDS-WMAN) - Ahmed, Syed Muqtar; Sattar, Syed Abdul (International Journal of Computer Sciences and Engineering, 2025)
Presenting cutting edge research- A mobile Adhoc network is a collection of wireless devices in which nodes interact with each other in a tentative topology without using pre-defined infrastructure. Almost all networks are protected using multilayer firewalls and encryption methods, but many of them are not so effective. Therefore we proposed a Robust Design of Intrusion Detection System in Wireless Mobile Adhoc Network (RDIDS-WMAN) to detect anomalies for multi-hop networks. The purpose of this paper is to design a detail architecture of Analysis Process that operates on simple rules including four different phases namely Event management, Authentication, Duplicate request generation and Message alert monitoring phase to detect the malicious node. This paper also conducted the simulation of proposed RDIDS-WMAN with a combination of AODV protocol to show its effectiveness and resists the attacks. Meanwhile, the performance of network, such as Packet Delivery Ratio, Average End-to-End delay, Throughput and Packet Drop Ratio is tolerable according to the NS-2.35 simulation results. Our solution also uses an authentication process with hash method